Five Organizational Features That Enable Successful Interdisciplinary Marine Research - Blythe, Jessica; Cvitanovic, Christopher (Frontiers in Marine Science, 2020)
To generate innovative solutions for marine sustainability challenges, scientists, policymakers, and funders are increasingly calling for interdisciplinary research that transcends disciplinary boundaries. However, challenges associated with doing interdisciplinary research persist and undermine progress towards tackling the complex challenges faced by marine social-ecological systems. One barrier for engaging in effective interdisciplinary research is a lack of understanding about the institutional capacities that support interdisciplinary knowledge production. Based on in-depth qualitative interviews with members of the Centre for Marine Socio-ecology in Australia, we identify five principles that underpin effective interdisciplinary research organisations. The principles are: 1) support female leadership; 2) forge partnerships outside of academia; 3) develop impact-based performance metrics; 4) focus on long-term funding; and 5) cultivate a visible brand. Going forward, these principles could be used to inform organizational design that transforms institutional barriers into enablers of innovative interdisciplinary research for more sustainable, desirable, and equitable futures.